ANALISIS URAIAN TUGAS OPERATOR SEKOLAH DI SLTP SE-KABUPATEN SOLOK - Tahany Nabila Putri; Rusdinal Rusdinal; Hade Afriansyah; Enceria Damanik (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the job descriptions of school operators at junior high schools (SLTP) in Solok Regency based on task clarity, responsibility, and authority. Methods: This study employed a quantitative descriptive approach. The population consisted of 110 school operators, with 53 respondents selected using simple random sampling with a 10% margin of error. Data were collected using a 28-item Likert-scale questionnaire and analyzed using mean, standard deviation, and Respondent Achievement Level (TCR). Results: The findings show that the job descriptions of school operators were categorized as “Agree,” with a mean score of 4.28 and TCR of 85.56%. Responsibility obtained the highest score (mean 4.32; TCR 86.33%), followed by task clarity (mean 4.27; TCR 85.36%) and authority (mean 4.25; TCR 84.98%). Novelty: This study provides a specific description of school operators’ job descriptions based on task clarity, responsibility, and authority, which have received limited attention in previous studies on school administrative personnel. The findings indicate that clear job descriptions are important for supporting the effective and accountable implementation of school operator duties.